2017
DOI: 10.24289/ijsser.317678
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the desserts; which are hosmerim, cheese halva, kunafah produced in Turkish cuisine-in aspect of tourism

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Shiga toxins (stx1 and stx2), enterohemolysin (hlyA), and intimin (eaeA) are virulence factors that play a key role in the development of these disorders [13]. There are additional studies focusing on E. coli and other pathogens in RTE foods [14].…”
Section: Introductionmentioning
confidence: 99%
“…Shiga toxins (stx1 and stx2), enterohemolysin (hlyA), and intimin (eaeA) are virulence factors that play a key role in the development of these disorders [13]. There are additional studies focusing on E. coli and other pathogens in RTE foods [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are studies focusing on the presence of E. coli and other pathogens in RTE foods (Bingol et al, 2008;Ateş et al, 2011;Cokal et al, 2012;Taban, 2012;Delikanli et al, 2014;Secim et al, 2017), to our knowledge, this study is the first report concerning the detection and genotyping of pathogenic E. coli serotypes in cheese halva, meatless cig kofte, Russian salad and stuffed mussel in Turkey. Studies on the pathogenic E. coli serotypes in RTE foods need to continue in order to complete food safety requires.…”
Section: Introductionmentioning
confidence: 77%
“…According to literature screening, there is no research related to E. coli O157:H7 in cheese halva in Turkey. Nevertheless Secim et al (2017) investigated presence of E. coli in cheese halva samples and reported no contamination. The presence of E.coli has been investigated in cheese desserts in some studies; Cokal et al (2012) and Secim et al (2017) reported that no E. coli contamination in Hosmerim desserts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Türkiye, the recognition of many MJEN MANAS Journal of Engineering, Volume 12 (Issue 1) © 2024 www.journals.manas.edu.kg traditional foods is limited to the rural regions where they are produced. Consequently, due to urbanization, awareness of these foods is gradually diminishing among younger generations, leading to insufficient utilization of these traditional products, which possess significant potential for added value [5][6]. "Erzurum cheese halva," bearing a protected geographical indication, is a traditional delicacy exclusive to the Erzurum province.…”
Section: Introductionmentioning
confidence: 99%